2017
DOI: 10.1161/strokeaha.117.016705
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 (Programmed Death Ligand 1) Protects Against Experimental Intracerebral Hemorrhage–Induced Brain Injury

Abstract: Background and Purpose— Intracerebral hemorrhage (ICH) is a neurologically destructive stroke, for which no valid treatment is available. This preclinical study examined the therapeutic effect of PD-L1 (programmed death ligand 1), a B7 family member and a ligand for both PD-1 (programmed death 1) and B7-1 (CD80), in a murine ICH model. Methods— ICH was induced by injecting autologous blood into 252 male C57BL/6 and Rag1 −/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Manipulation of PD-1:PD-L1/2 pathway is considered a potential therapeutic approach for treating autoimmune diseases ( 15 ). Impact of PD-L:PD-1 axis on differentiation of CD4 + T cell subsets has been reported in previous studies ( 32 , 56 , 57 ). In this study, we also observed that the increased expression of PD-1 in CD4 + T cells in T. spiralis -infected mice and knockout of PD-1 resulted in the recovery of inhibited CD4 + T cell proliferation caused by nematode infection, indicating PD-1 is involved in the nematode infection caused regulation of CD4 + T cells.…”
Section: Discussionsupporting
confidence: 75%
“…Manipulation of PD-1:PD-L1/2 pathway is considered a potential therapeutic approach for treating autoimmune diseases ( 15 ). Impact of PD-L:PD-1 axis on differentiation of CD4 + T cell subsets has been reported in previous studies ( 32 , 56 , 57 ). In this study, we also observed that the increased expression of PD-1 in CD4 + T cells in T. spiralis -infected mice and knockout of PD-1 resulted in the recovery of inhibited CD4 + T cell proliferation caused by nematode infection, indicating PD-1 is involved in the nematode infection caused regulation of CD4 + T cells.…”
Section: Discussionsupporting
confidence: 75%
“…The overall pro-inflammatory cytokine production was decreased with down-regulation of IL-1β, IL-6, and TNF-α, and upregulation of IL-10. 126 As mentioned earlier, microglia polarization plays a very important role in ICH-induced secondary brain injury. In response to ICH, selective polarization to the pro-inflammatory type occurs.…”
Section: Programmed Death-1 Pathwaymentioning
confidence: 85%
“…125 PD-L1 administration significantly attenuated the severity of neurologic deficits, decreased cerebral edema by decreasing brain water content, and decreased hemorrhage volume. 126 PD-L1 also downsized the number of CD4 + T cells infiltrating the brain and overall percentages of Th1 and Th17 cells while increasing the overall percentages of the Th2 and regulatory T cells. The overall pro-inflammatory cytokine production was decreased with down-regulation of IL-1β, IL-6, and TNF-α, and upregulation of IL-10.…”
Section: Programmed Death-1 Pathwaymentioning
confidence: 92%
“…While these results suggested that Cx43KO astrocytes adopted a pro-inflammatory profile, most canonical panreactive astrocyte markers such as Lcn2 (Lipocalin-2), Vim (Vimentin) or Gfap were not upregulated in Cx43KO astrocytes [ 5 , 6 ]. In addition, several anti-inflammatory markers were upregulated, among which the complement decay-accelerating factor CD55 and the membrane receptor CD274 which inhibits T-cell proliferation by blocking cell cycle progression and cytokine production [ 25 ] ( Table 1 ). The Toll-like receptor Tlr4 was also downregulated in Cx43KO astrocytes ( Supplementary Table S2 ), thus possibly reducing astrocyte capacity to activate an innate immune response [ 26 ].…”
Section: Resultsmentioning
confidence: 99%